The Effect of Fishbone Method on Students Writing Ability of Report Text - Ilza Emilda; Hamzah Hamzah (Journal of English Language Teaching, 2021)
This research was a quasi-experimental study, which aimed to find out the empirical evidence of the effect of using Fishbone method on students’ writing ability of report text. The population of this research was all students of class XI of SMA Negeri 1 Tanjung Raya. The researcherused the sample of two classes that were chosen as the sample by using cluster random sampling. The samples were taken from 25 students of experimental group (class XI MIA-1) and 25 students of control group (class XI MIA-3). The instrument of this research was a writing test. T-test was used to analyze the data collected in this research. The result of T-test indicated thatsig (2-tailed) of the experimental class (0.000) was lower than sig  or tobservedwas higher than ttable (). While sig (2-tailed) of the control class (0.000) was lower than sig  or tobservedwas higher than ttable(. It can be concluded that the students who are taught by using the Fishbone method have higher results than the students who are taught by using the conventional teaching method. It means the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Thus, Fishbone method produces higher results on students' writing ability of report text rather than conventional teaching method.